Nuclear Spectroscopic Properties within a Selfconsistent Multiphonon Approach. (June 2016) - De Gregorio, G; Knapp, F; Iudice, N Lo; Veselý, P; Andreozzi, F; Porrino, A
Abstract: The equation of motion phonon method is adopted to investigate the dipole response in neutron rich nuclei. The calculation is carried out in a space spanned by one- and two-phonon basis states. It makes direct use of a nucleon-nucleon optimized chiral potential complemented with a density dependent term simulating a three-body force and is fully selfconsistent. The inclusion of the two-phonon states induces a pronounced fragmentation of both giant and pygmy resonances consistently with recent experiments.